Application of Canine-Derived Enterococcus faecium DSM 32820 in Dogs with Acute Idiopathic Diarrhoea - Kubašová Ivana; Štempelová Lucia; Maďari Aladár; Bujňáková Dobroslava; Micenková Lenka; Strompfová Viola (Acta Veterinaria, 2022)
Modulation of the intestinal microbiota through the application of probiotic bacteria is currently one possible way to improve gastrointestinal health in dogs. Knowledge on the efficacy of lactic acid bacteria in a diarrhoeic disorder of dogs is still spreading; however, the used or commercialized strains are often not of canine origin. In this study, E. faecium DSM 32820 strain (a canine isolate selected in our laboratory based on safety and probiotic criteria) was fed to nine dogs suffering from acute non-haemorrhagic diarrhoea at a dose of 1×109 CFU/ml for 7 days. Samples of feces and blood were taken on day 0 and 7. Evaluation of the CIBDAI (Canine Intestinal Bowel Disease activity index) score showed significantly lower vomiting frequency, stool frequency, stool consistency and weight loss at day 7 compared to day 0 (P<0.05). The 16S rRNA gene analysis revealed Firmicutes as the predominant phylum on both sampling days (72.0% vs. 67.9%, day 0 and 7) followed by Proteobacteria (13.4% vs. 6.0%), Actinobacteria (10.0% vs 13.5%), Fusobacteria (4.2% vs. 2.3%) and Bacteroidetes (0.4% vs. 10.4%). The abundance of family Erysipelotrichiaceae was higher on day 7 compared to the initial levels (P<0.05). Among 19 detected fecal enzymatic activities, five (α-chymotrypsin, β-glucuronidase, α-fucosidase, β-galactosidase, N-acetyl-glucosaminidase) were changed (P<0.05). After the application of the DSM 32820 strain, mean fecal dry matter was significantly higher on day 7 compared to baseline (P< 0.05). Although hematological and biochemical parameters in the blood were not significantly different on average, individual values of certain parameters in several dogs were improved.